2006
DOI: 10.1111/j.1600-0897.2006.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Natural Immune Response against Altered Fibroblasts in the Development of Post‐Operative Adhesions

Abstract: These results demonstrate that ATF are more susceptible to lymphocyte-mediated elimination than NPF and the development of adhesions despite this could be explained by either impaired or overwhelmed autologous natural immune response against reactive fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
3
12
0
1
Order By: Relevance
“…This is in line with a study by Alpay et al investigating normal peritoneal fibroblasts and adhesion tissue fibroblast expression patterns of immune response-related markers and lymphokine-activated killer cell-mediated fibroblast elimination in vitro [2]. The authors pointed out that adhesion tissue fibroblasts were more predisposed to lymphocyte-mediated elimination than normal peritoneal fibroblasts, and they supposed that the development of adhesions despite this could be explained by either impaired or overwhelmed autologous natural immune response against reactive fibroblasts [2]. In a previous study, we found T lymphocytes irrespective of the adhesions age, and interestingly, even in long-term persistent human peritoneal adhesions [6].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with a study by Alpay et al investigating normal peritoneal fibroblasts and adhesion tissue fibroblast expression patterns of immune response-related markers and lymphokine-activated killer cell-mediated fibroblast elimination in vitro [2]. The authors pointed out that adhesion tissue fibroblasts were more predisposed to lymphocyte-mediated elimination than normal peritoneal fibroblasts, and they supposed that the development of adhesions despite this could be explained by either impaired or overwhelmed autologous natural immune response against reactive fibroblasts [2]. In a previous study, we found T lymphocytes irrespective of the adhesions age, and interestingly, even in long-term persistent human peritoneal adhesions [6].…”
Section: Discussionsupporting
confidence: 91%
“…The same study group demonstrated that CD4(+) alpha beta T lymphocytes are essential for the development of peritoneal adhesions and provided evidence that the cells orchestrating adhesion formation are of the Th1 phenotype [38]. This is in line with a study by Alpay et al investigating normal peritoneal fibroblasts and adhesion tissue fibroblast expression patterns of immune response-related markers and lymphokine-activated killer cell-mediated fibroblast elimination in vitro [2]. The authors pointed out that adhesion tissue fibroblasts were more predisposed to lymphocyte-mediated elimination than normal peritoneal fibroblasts, and they supposed that the development of adhesions despite this could be explained by either impaired or overwhelmed autologous natural immune response against reactive fibroblasts [2].…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, it is unclear whether the origin of the mesothelial cells and the culture conditions could be important or whether these cells actively secrete substances in the peritoneal fluid. We cannot even ascertain that the effect is specific for mesothelial cells since Alpay et al demonstrated that also fibroblasts display different immunologic characteristics with an effect on adhesion formation [28].…”
Section: Discussionmentioning
confidence: 98%
“…Staining was performed according to published methods (11,12). Peripheral blood mononuclear cells from two healthy donors were used to generate LAK cells in the presence of interleukin 2 and interleukin 15.…”
mentioning
confidence: 99%
“…Peripheral blood mononuclear cells from two healthy donors were used to generate LAK cells in the presence of interleukin 2 and interleukin 15. The LAK cell-mediated fibroblast elimination was studied by our established flow cytometric cell-mediated cytotoxicity assay (11,13).…”
mentioning
confidence: 99%